Acupuncture combined with mouse nerve growth factor in the treatment of peripheral facial palsies: systematic review and meta-analysis - Hu, Yufei; Liu, Yijie; Diao, Zhihao; Jiang, Yifan; Zhang, Longtao; Ma, Yuxia; Zhang, Na (Frontiers in Medicine, 2025)
BackgroundPeripheral facial palsies (PFP) had been listed as a dominant disease of acupuncture. Numerous researchers had utilized acupuncture in conjunction with mouse nerve growth factor (mNGF) for PFP. However, there is little relevant systematic and standardized evidence-based medicine, and the efficacy of this treatment modality is currently controversial.ObjectiveTo systematically evaluate the clinical efficacy of acupuncture combined with mNGF for PFP.MethodsWe systematically searched seven databases from their inception to 10 May 2024 to identify relevant randomized controlled trials (RCTs). The Cochrane Risk of Bias tool was used to evaluate the quality of the included literature, RevMan 5.4 software was used to test for heterogeneity, Stata v.15. SE software was used to perform egger test and sensitivity analysis.ResultsResults from 36 RCTs involving 2,750 patients showed that compared with single therapy, combination therapy can improve scores in the overall effective rate (RR = 1.21, 95% CI [1.17, 1.25], p < 0.001), Facial disability index-physical (FDIP) score (MD = 3.31, 95% CI [0.01, 6.60], p = 0.05),facial nerve conduction velocity (MD = 0.54, 95% CI [0.02, 1.07], p = 0.04), Compound Muscle Action Potential (CMAP) amplitude (MD = 0.29, 95% CI [0.10, 0.48], p = 0.003), Portmann score (MD = 1.16, 95% CI [0.88, 1.44], p < 0.001) and reduce scores in Sunnybrook Facial Grading System (SFGS) static score (MD = −2.86, 95% CI [−3.89, −1.83], p < 0.001), House-Brackmann Facial Nerve Function Classification score (MD = −0.68, 95% CI [−1.01, −0.36], p < 0.001), Facial disability index-social (FDIS) score (MD = −5.26, 95% CI [−7.60, −2.91], p < 0.001), and R1 latency (MD = −0.58, 95% CI [−0.97, −0.18], p = 0.004). However, there was no significant difference in SFGS dynamic functional score.ConclusionThese findings suggest that the treatment of PFP with acupuncture combined with mNGF has a certain superiority over acupuncture alone or mNGF alone. It can be used as one of the therapeutic strategies for the treatment of PFP. However, the certainty and external authenticity of the evidence is limited due to the low quality of the methods and geographical concentration of the included studies.Systematic review registrationIdentifier CRD42024548516.